To expand the expression \((3x + 8)(3x^2 + x - 1)\), we'll use the distributive property (also known as the FOIL method for binomials). We'll multiply each term in the first polynomial by each term in the second polynomial.
-
Multiply \(3x\) by each term in \(3x^2 + x - 1\):
- \(3x \cdot 3x^2 = 9x^3\)
- \(3x \cdot x = 3x^2\)
- \(3x \cdot (-1) = -3x\)
So, this part gives us: \[ 9x^3 + 3x^2 - 3x \]
-
Multiply \(8\) by each term in \(3x^2 + x - 1\):
- \(8 \cdot 3x^2 = 24x^2\)
- \(8 \cdot x = 8x\)
- \(8 \cdot (-1) = -8\)
So, this part gives us: \[ 24x^2 + 8x - 8 \]
-
Combine all the terms together: \[ 9x^3 + 3x^2 - 3x + 24x^2 + 8x - 8 \]
-
Combine like terms:
- \(9x^3\)
- Combine \(3x^2 + 24x^2 = 27x^2\)
- Combine \(-3x + 8x = 5x\)
- The constant term is \(-8\)
So, the complete expanded expression is: \[ \boxed{9x^3 + 27x^2 + 5x - 8} \]